Microplastics contamination of wild and farmed Goldspot mullets (Chelon parsia) in Khulna coastal region of Bangladesh - Rupa Labanna Rahman; Partho Protim Barman; Diponkor Adikari; Thorna Rani Das; Israt Nur Suravi; Mafia Akter; Sultan Al Nahian; Shristi Datta; Al Mamun; MS Islam (Regional Studies in Marine Science, 2025)

Stock Assessment of Long Whisker Catfish (Mystus gulio): Ensuring the Fisheries’ Sustainability in the Sundarbans Mangrove, Bangladesh - Md. Tanvir Rahman Ovi; Tanni Sarkar; Dwipika Gope; Rayhan Ahmod; Sanzib Kumar Barman; Md. Mostafa Shamsuzzaman; Mohammad Mojibul Hoque Mozumder; Petra Schneider; Partho Protim Barman (Fishes, 2025)
The world’s largest mangrove, Sundarbans, Bangladesh, is the habitat of the euryhaline catfish Nona Tengra (Mystus gulio). This study aimed to assess the stock status of M. gulio and provide reference points for sustainable fisheries’ management. One-year length–frequency (LF) data were collected from the Sundarbans region of Bangladesh and analyzed using the Length-Based Bayesian Biomass (LBB) method and the Length-Based Spawning Potential Ratio (LBSPR) model. The findings showed healthy biomass (B/BMSY = 1.2), with 57% of the wild stock of this species being harvested (B/B0 = 0.43). The calculated fishing mortality ratio indicated the underfishing conditions (F/M = 0.9). Safe exploitation (E = 0.46) was depicted, as E was smaller than the permitted level of 0.5. The value of capture length (Lc = 12.8 cm) was larger than the optimum capture length (Lc_opt = 10.0 cm) and the optimum length for maximum yield per recruit (Lopt = 12.0 cm) and larger than the maturity length (Lm = 9.16 cm), indicating the capture of mature individuals. The calculated Spawning Potential Ratio (SPR = 48%) was higher than the target reference points (SPR = 40%). This research evaluated the sustainable stock status. Although the margin between Lc_opt and Lm is very narrow, setting the minimum capture size at Lopt would be a conservative buffer to ensure long-term sustainability. The recommended minimum harvest size is 12 cm for M. gulio. Current fishing gear selectivity can ensure the sustainability of M. gulio in Sundarbans, Bangladesh; however, maintaining current fishing practice through careful management is suggested. Further assessments with length-based and other low-data methods should be conducted to refine exploitation estimates and trends.

Stock Assessment of Marine Elasmobranchs (Sharks and Rays) in the Bay of Bengal, Bangladesh - Dwipika Gope; Md. Mostafa Shamsuzzaman; Md. Shahidul Islam; Tanni Sarkar; Alaka Shah Roy; Mohammad Mojibul Hoque Mozumder; Partho Protim Barman (Journal of Marine Science and Engineering, 2025)
The Bay of Bengal (BoB) is a global hub for marine elasmobranchs, particularly sharks and rays. These apex predators maintain and structure the balanced marine ecosystem and food webs. Marine elasmobranchs in Bangladesh are under-researched and under-managed, and face threats such as habitat degradation, global warming, pollution, illegal fishing, and overexploitation. This study aimed to evaluate the stock status of marine elasmobranches in the Bay of Bengal (BoB), Bangladesh. This research used catch and effort (CE) data for a period of 21 years (2002–2022). Both the Monte Carlo CMSY and BSM models were applied to assess biomass, exploitation rates, and sustainable yields. The BSM estimated a maximum carrying capacity (k) of 134,000 mt, which is larger than the CMSY estimate of 119,000 mt. The estimated intrinsic annual growth (r) from CMSY was 0.282. The MSY values ranged from 5110 mt (BSM) to 8420 mt (CMSY), with BSM indicating overexploitation, as the 2022 catch (7017 mt) exceeded the BSM-derived MSY. Both models suggested depleted and overfishing stock conditions, with B/BMSY ratios 1.0. Effective management is crucial to prevent overfishing and ensure sustainable practices. Elasmobranch catches must be kept below the BSM-estimated maximum sustainable yield (MSY) of 5110 metric tons with fishing pressure maintained at or below F/FMSY = 1.0. It is vital to regulate illegal and unlicensed fishing activities. Because of the aggregation of CE data, the results should be interpreted cautiously and never serve as a substitute for species-level assessments.

A comprehensive scenario of heavy metals pollution in the rivers of Bangladesh during the last two decades - Debasish Pandit; Mohammad Mahfujul Haque; Md. Simul Bhuyan; Ahmed Harun-Al-Rashid; Partho Protim Barman; Rana Roy; Bishwajit Sarker; Md. Khalid Saifullah; Mrityunjoy Kunda (Environmental Science and Pollution Research, 2024)

Estimating Stock Status and Biological Reference Points of the Sardine Fishery Using the Surplus Production Model from the Bay of Bengal, Bangladesh - Rokeya Sultana; Qun Liu; Md. Abdullah Al-Mamun; Partho Protim Barman; Md. Mostafa Shamsuzzaman; Suman Barua (Journal of Marine Science and Engineering, 2023)
This research examined the biological reference points (BRPs) and stock status of the sardine fishery in the Bay of Bengal (BoB), Bangladesh, to determine the sustainability of this resource. The Monte Carlo method (CMSY), the Bayesian state-space Schaefer surplus production model (BSM), and the ASPIC (a Stock Production Model Incorporating Covariates) software suite, were used to analyze catch–effort data obtained from the Yearbook of Fisheries Statistics of Bangladesh. All models derived maximum sustainable yields (MSY) ranging from 37,900 to 41,280 t, which is quite near to the catch from the latest year (38,051 t in 2020), indicating the fully exploited status of sardines. The estimated B FMSY values from the BSM and Schaefer models indicate a poor biomass and an unsafe fishing status. For Schaefer and BSM, the calculated F/FMSY values were 1.07 and 1.06, and the B/BMSY values were 0.92 and 0.75, which also indicate the overexploited status of the sardine fishery in the BoB, Bangladesh. This information will aid in developing management strategies and conservation policies for the sustainability and rebuilding of this commercially important resource in the BoB on the Bangladesh coast.

Fisheries Reference Point and Stock Status of Croaker Fishery (Sciaenidae) Exploited from the Bay of Bengal, Bangladesh - Partho Protim Barman; Md. Mostafa Shamsuzzaman; Petra Schneider; Mohammad Mojibul Hoque Mozumder; Qun Liu (Journal of Marine Science and Engineering, 2022)
This research evaluated fisheries reference points and stock status to assess the sustainability of the croaker fishery (Sciaenidae) from the Bay of Bengal (BoB), Bangladesh. Sixteen years (2001–2016) of catch-effort data were analyzed using two surplus production models (Schaefer and Fox), the Monte Carlo method (CMSY) and the Bayesian state-space Schaefer surplus production model (BSM) method. This research applies a Stock–Production Model Incorporating Covariates (ASPIC) software package to run the Schaefer and Fox model. The maximum sustainable yield (MSY) produced by all models ranged from 33,900 to 35,900 metric tons (mt), which is very close to last year’s catch (33,768 mt in 2016). The estimated B > BMSY and F

Stock Assessment of Exploited Sardine Populations from Northeastern Bay of Bengal Water, Bangladesh Using the Length-Based Bayesian Biomass (LBB) Method - Partho Protim Barman; Qun Liu; Md. Abdullah Al-Mamun; Petra Schneider; Mohammad Mojibul Hoque Mozumder (Journal of Marine Science and Engineering, 2021)
Stock assessment is necessary to understand the status of fishery stocks. However, for the data-poor fishery, it is very challenging to assess the stock status. The length-based Bayesian biomass (LBB) technique is one of the most powerful methods to assess the data-poor fisheries resources that need simple length frequency (LF) data. Addressing the present gap, this study aimed to assess the stock status of three sardines (Sardinella fimbriata, Dussumieria acuta, and D. elopsoides) in the Bay of Bengal (BoB), Bangladesh using the LBB method. The estimated relative biomass for S. fimbriata was B/B0 BMSY/B0 for D. acuta and D. elopsoides indicates healthy biomass. Additionally, for S. fimbriata, the length at first landing was smaller than the optimum length at first landing (Lc Lc_opt). Therefore, increasing the mesh size of fishing gears may help to ensure the long-term viability of sardine populations in the BoB, Bangladesh.

A preliminary snapshot of the trophic model and ecosystem attributes of Kaptai reservoir ecosystem, Bangladesh - Mst Halima Khatun; Partho Protim Barman; Jundong Yi; Saymuna Tarin Lupa; Md Mahiuddin Zahangir; Qun Liu (Journal of Oceanology and Limnology, 2021)